Teachers' Strategies for Improving Third-Grade Students' Ability to Memorize Short Surahs of the Qur'an at Al-Kiswah Islamic Elementary School, Bengkulu City - Atik Kurniawati; Yayu Piola Andita Putri; Kasmantoni; Andre Taulani Sandi; Heny Friantary (Yayasan Azhar Amanaa Yogyakarta, 2025)
The ability to memorize short surahs of the Qur’an is an important competency for elementary school students. This study aimed to analyze teachers’ strategies for improving the memorization ability of third-grade students at Al-Kiswah Islamic Elementary School, Bengkulu City, and to identify the factors influencing its implementation. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation involving teachers and 28 students. The findings showed that teachers applied the talaqqi, simai, and wahdah methods, supported by motivation, rewards, and murojaah activities. Supporting factors included teacher guidance, parental support, and student discipline, while inhibiting factors consisted of low concentration, limited self-awareness, insufficient memorization time, and students’ physical condition. The study concludes that these strategies effectively improved students’ ability to memorize short surahs of the Qur’an.